Iron Oxidation and Core Formation in Recombinant Heteropolymeric Human Ferritins - Mehlenbacher, Matthew (Biochemistry, 2017)
In animals, the iron storage and detoxification protein, ferritin, is composed of two functionally and genetically distinct subunit types, H (heavy) and L (light), which co-assemble in various ratios with tissue specific distributions to form shell-like protein structures of 24 subunits within which a mineralized iron core is stored. The H-subunit possesses a ferroxidase center (FC) that catalyzes Fe(II) oxidation, whereas the L-subunit does not. To assess the role of the L-subunit in iron oxidation and core formation, two human recombinant heteropolymeric ferritins, designated H-rich and L-rich with ratios of ~20H:4L and ~22L:2H, respectively, were employed and compared to the human homopolymeric H-subunit ferritin (HuHF). These heteropolymeric ferritins have a composition similar to the composition of those found in hearts and brains (i.e., H-rich) and in livers and spleens (i.e., L-rich). As for HuHF, iron oxidation in H-rich ferritin was found to proceed with a 2:1 Fe(II):O(2) stoichiometry at an iron level of 2 Fe(II) atoms/H-subunit with the generation of H(2)O(2). The H(2)O(2) reacted with additional Fe(II) in a 2:1 Fe(II):H(2)O(2) ratio, thus avoiding the production of hydroxyl radical. A μ-1,2-peroxo-diFe(III) intermediate was observed at the FC of H-rich ferritin as for HuHF. Importantly, the H-rich protein regenerated full ferroxidase activity more rapidly than HuHF did and additionally formed larger iron cores, indicating dual roles for the L-subunit in facilitating iron turnover at the FC and in mineralization of the core. The L-rich ferritin, while also facilitating iron oxidation at the FC, additionally promoted oxidation at the mineral surface once the iron binding capacity of the FC was exceeded.